Komunikasi Politik (Model Komunikasi Politik Antar Fraksi dalam Pembentukan Norma UU Pilkada Secara Demokratis) - Putri, Rosiana Eka; , Dr. Aidul Fitriciada Azhari, SH., M.Hum; , Dr. Nurhadiantomo (2017)
This study aimed to provide insight about political communication process among fraction on the creation of Local Leader Election (LLE) Act, the influence of political communication process among fraction on the creation of LLE Act, and offer a model of an effective political communication process among fraction on the creation of Local Leader Election (LLE) Act. This was a qualitative research, with a sociological juridical approach. Secondary data and primary data which collected using observation, interviews, and document study, were analyzed using interactive data analysis process. The conclusions of this study, among others 1) there were several political communication process among fraction on the creation of LLE Act, such as ideation, encoding, message delivery, decoding, feedback, and validation, 2) political communication process among fraction on the creation of LLE Act were affected the LLE Act norm building, especially in decoding and feedback processes, and 3) the model of an effective political communication process among fraction on the creation of LLE Act created by inserting public participation into the process and using circular political communication on the creation of LLE Act. Keywords: Circular, Feedback, LLE Act, Political Communication.